Ciprofloxacin and pegylated G-CSF combined therapy mitigates brain hemorrhage and mortality induced by ionizing irradiation - Kiang, Juliann G.; Cannon, Georgetta; Olson, Matthew G.; Zhai, Min; Woods, Akeylah K.; Xu, Feng; Lin, Bin; Li, Xianghong; Hull, Lisa; Jiang, Suping; Xiao, Mang (Frontiers in Public Health, 2023)
Introduction Brain hemorrhage was found between 13 and 16 days after acute whole-body 9.5 Gy 60Co-γ irradiation (IR). This study tested countermeasures mitigating brain hemorrhage and increasing survival from IR. Previously, we found that pegylated G-CSF therapy (PEG) (i.e., Neulasta®, an FDA-approved drug) improved survival post-IR by 20–40%. This study investigated whether Ciprofloxacin (CIP) could enhance PEG-induced survival and whether IR-induced brain hemorrhage could be mitigated by PEG alone or combined with CIP. Methods B6D2F1 female mice were exposed to 60Co-γ-radiation. CIP was fed to mice for 21 days. PEG was injected on days 1, 8, and 15. 30-day survival and weight loss were studied in mice treated with vehicles, CIP, PEG, or PEG + CIP. For the early time point study, blood and sternums on days 2, 4, 9, and 15 and brains on day 15 post-IR were collected. Platelet numbers, brain hemorrhage, and histopathology were analyzed. The cerebellum/pons/medulla oblongata were detected with glial fibrillary acidic protein (GFAP), p53, p16, interleukin-18 (IL-18), ICAM1, Claudin 2, ZO-1, and complement protein 3 (C3). Results CIP + PEG enhanced survival after IR by 85% vs. the 30% improvement by PEG alone. IR depleted platelets, which was mitigated by PEG or CIP + PEG. Brain hemorrhage, both surface and intracranial, was observed, whereas the sham mice displayed no hemorrhage. CIP or CIP + PEG significantly mitigated brain hemorrhage. IR reduced GFAP levels that were recovered by CIP or CIP + PEG, but not by PEG alone. IR increased IL-18 levels on day 4 only, which was inhibited by CIP alone, PEG alone, or PEG + CIP. IR increased C3 on day 4 and day 15 and that coincided with the occurrence of brain hemorrhage on day 15. IR increased phosphorylated p53 and p53 levels, which was mitigated by CIP, PEG or PEG + CIP. P16, Claudin 2, and ZO-1 were not altered; ICAM1 was increased. Discussion CIP + PEG enhanced survival post-IR more than PEG alone. The Concurrence of brain hemorrhage, C3 increases and p53 activation post-IR suggests their involvement in the IR-induced brain impairment. CIP + PEG effectively mitigated the brain lesions, suggesting effectiveness of CIP + PEG therapy for treating the IR-induced brain hemorrhage by recovering GFAP and platelets and reducing C3 and p53.